Effect of Moxibustion on Behavioral Changes and Expression of APP and BACE1 in Hippocampus of SAMP8 Mice. (14th August 2020) - Ha, Lue; Yang, Bin; Wang, Shaosong; An, Yu; Wang, Hao; Cui, Yingxue
Abstract : Objective . To observe the effect of moxibustion on cognitive function of aging mice, to observe the effect of moxibustion on protein and gene expression of APP metabolism pathway, and to explore the mechanism of action in moxibustion. Methods . 24 SAMP8 were randomly divided into 2 groups (12 in each group): moxibustion group and model group. 12 SAMR1 mice were used as blank controls. Mice in the moxibustion group were treated with moxibustion for 8 weeks, 10 minutes each time, 5 times a week, and for a total of 8 weeks. The model group and the blank group were treated with sham-moxibustion. Behavior tests were used to detect the learning and memory ability of each group of mice. Immunohistochemical, western blot, and RT-PCR were used to detect the protein and mRNA expression of APP and BACE1. Furthermore, the expressions of miR-29 and miR-101 were observed by RT-PCR method to explore the mechanism of moxibustion at the genetic level. Results . In this study, relative to normal mice, we found that aging mice showed behavioral changes consistent with the onset of AD. However, moxibustion interventions were able to mitigate these effects to some degree in aging mice. In addition, moxibustion was proved to regulate APP metabolism pathway at protein and gene level through molecular biology tests. Conclusion . The data suggest that the effect of moxibustion intervention on cognitive function in aging mice is related to the regulation of genes and proteins involved in APP metabolism pathway; this may be a potential target for treating Alzheimer's disease.